Microeconomics - Karlan, Dean S. (McGraw-Hill Education, 2014)
In this book, we will introduce you to the tools economists are using to tackle some of the world's biggest challenges, from health care reform, to climate change, to lifting people out of provetty. Of course, these tools are not just for taking on causes worthy of Nobel Prizes. Economics can also hepl you become a savvier consumer, successfully launch a new cell phone aap, or simply make decisions about how to spend your time and money. Throughout this book, we promise to ask you not just to memorize theories, but also to apply the idears you read about the everyday decisions you face in your own life